QUALITÉ ET POLLUTION DES EAUX D’UN HYDROSYSTÈME LITTORAL TROPICAL : CAS DU SYSTÈME LAGUNAIRE DE LOMÉ, TOGO - Ayah, Massabalo; Grybos, Malgorzata; Tampo, Lallébila; Bawa, Limam Moctar; Bril, Hubert; Djaneye-Boundjou, Gbandi (European Scientific Journal, ESJ, 2015)
This study was conducted to evaluate the physicochemical quality and heavy metals (HM) in the water of Lomé lagoon system. The conductivity, pH, nitrogen, phosphorus, organic matter and HM were determined by AFNOR methods. The results showed that the waters of Lomé lagoon system have generally pH close to neutral (pH between 7.34 and 8.5). However, the balance of the water in the equilibrum canal has an acid pH (pH 6.53). The levels of nitrogen and phosphorus are relatively high 1.27 mg/L phosphorus against 0.15 mg/L in natural waters. Dissolved organic matter is higher at the site C4 over the entire lagoon system. The East Lake E3 and E1 sites recorded a high rate of mineralization with 2536 mg/L of dissolved salts. The contents of the major ions such as Ca2+, Na+, K+, Mg2+,Cl-, NO3-, SO42- and HCO3- helped to highlight the nature of brackish water of Lomé lagoon system. The material suspended (77 mg/L) and turbidity (35 NTU) are also very high in the waters of the equilibrium canal. C4 websites, C2, E3, O11, O5 and B3 have recorded the highest levels of HM. This indicates a potential bioavailability of HM in the waters of Lomé lagoon system. The degree of contamination and the interrelationships between the physical and chemical parameters of water and metallic micropollutants were confirmed by Principal Component Analysis (PCA).